Groups endorse ECG screening for athletes - Schnirring, L. (The Physician and Sportsmedicine, 2005)
Obstacles such as cost, staffing, and the likelihood of false-positives have prevented cardiac diagnostic tests such as 12-lead electrocardiography (ECG) from becoming a routine part of the preparticipation examination (PPE) in most countries, including the United States. Two international medical groups, however, have recently endorsed the inclusion of the 12-lead ECG in the PPE.